集学的治療が奏効した上顎歯肉無色素性悪性黒色腫の1例 - 西川, 雅也; 小原, 豪; 日比, 英晴; 山口, 聡; 市村, 典久; 山本, 憲幸 (日本口腔外科学会雑誌, 2021)
Immunostimulatory effects of immune checkpoint inhibitors and radiotherapy have attracted much attention in the treatment of malignant melanoma. We present a case in which multidisciplinary treatment including both of these produced a remarkable antitumor effect in an amelanotic malignant melanoma (AMM).A 67-year-old woman visited the nearby general hospital with the chief complaint of a mass in the gingiva of the left maxilla. The mass was resected; however, since it was diagnosed as spindle cell carcinoma, she was referred to our hospital for additional treatment. A partial resection of the left maxilla was performed under general anesthesia, and histopathological examination revealed AMM. Additional resections were performed for positive excisional margins; however, four months later metastasis was found in the left upper internal deep cervical lymph node. Although a left radical neck dissection was performed, ten months later recurrence was observed in the left side mandibular branch medial and the left first sternocostal joint. Twelve courses of Nivolumab and four courses of Ipilimumab were administered, then following radiotherapy (32 Gy) the tumor disappeared. Three years and one month have passed since the end of treatment, and there has been no recurrence or distant metastasis.